Influence of phenylphosphonate based flame retardant on epoxy/glass fiber reinforced composites (GRE): Flammability, mechanical and thermal stability properties. (1st February 2017) - Zhao, Xiaomin; Yang, Lingwei; Martin, Francisco Hueto; Zhang, Xiu-Qin; Wang, Rui; Wang, De-Yi
Abstract: In this work, flame-retardant glass fiber reinforced epoxy composites (FGRE) were successfully prepared via adding a novel phenylphosphonate-based flame retardant, N, N '-diamyl- p -phenylphosphonicdiamide (P-MA) into GRE. FGRE12 showed high LOI value of 33%. Meanwhile, FGRE12 passed V-0 rating in UL 94 test and the peak of heating release rate (pHRR) decreased by 54% in comparison with that of GRE. The flame-retardant efficiency of P-MA in GRE was compared with that in epoxy matrix (EP). Moreover, the influences of P-MA on mechanical and thermal stability properties of GRE were studied systemically. Dynamic mechanical analysis (DMA) studied the influence of P-MA on viscoelasticity of GRE. Fiber push-in test and three-point-bending test were used to evaluate the influence of P-MA on the EP matrix/fiber interface strength and interlamilnar shear strength, respectively. In addition, nanoindentation test was used to study the hardness and Young's modulus of EP matrix. The above results showed that the addition of P-MA did not affect the hardness of epoxy matrix and interfacial strength (epoxy matrix/glass fiber). The influence of P-MA on thermal stability of GRE was studied by thermalgravimetric analysis (TGA). These results would be very important in designing new generation multifunctional epoxy-based composite materials. Graphical abstract: Highlights: Phenylphosphonate-based flame retardant P-MA endow GRE with high self-extinguishing ability. Impact of flame retardant P-MA on mechanical properties of GRE was investigated. Fiber push-in test evaluated the interface strength between epoxy/glass fiber.